2000
DOI: 10.1177/000765030003900304
|View full text |Cite
|
Sign up to set email alerts
|

Cause-Related Marketing: Ethics and the Ecstatic

Abstract: This article evaluates the ethical implications of the practice of cause-related marketing (CRM). The authors note howCRMis consistent with a contemporary rhetoric that argues that consumers are displaying a developing interest in the social commitments of the corporate world. However, following the work of Zygmunt Bauman, the authors suggest that CRM actually threatens these sentiments. Of particular significance is its incorporation of a charitable act within an act of exchange that is mediated by marketing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 14 publications
1
56
0
4
Order By: Relevance
“…Its goal then is to enhance company revenues and sales or customer relationship by building the brand through the acquisition of, and association with the ethical dimension or social responsibility dimension (Murray and Montanari, 1986;Varadarajan and Menon, 1988). In a way, it seeks product differentiation by creating socially responsible attributes that affect company reputation (Smith and Higgins, 2000). As McWilliams and Siegel (2001, p. 120) have pointed out: ''support of cause related marketing creates a reputation that a firm is reliable and honest.…”
Section: Cause-related Marketingmentioning
confidence: 99%
“…Its goal then is to enhance company revenues and sales or customer relationship by building the brand through the acquisition of, and association with the ethical dimension or social responsibility dimension (Murray and Montanari, 1986;Varadarajan and Menon, 1988). In a way, it seeks product differentiation by creating socially responsible attributes that affect company reputation (Smith and Higgins, 2000). As McWilliams and Siegel (2001, p. 120) have pointed out: ''support of cause related marketing creates a reputation that a firm is reliable and honest.…”
Section: Cause-related Marketingmentioning
confidence: 99%
“…Rather, they clearly depict it as a strategic tool with which to achieve both social and corporate goals. 25,26 Nonetheless, consumers are often sceptical of commercial-nonprofit partnerships and their support is dependent on developing their trust in the sponsor. 27 Greater trust is achieved where alliances are strategic and firms establish a track record of socially responsible behaviour, demonstrating a long-term commitment to the causes supported.…”
Section: Cause-related Marketingmentioning
confidence: 99%
“…Furthermore, the focus of CSR research has shifted from ''why '' to ''what'' to ''how'', i.e., to adopt CSR practices most compatible to business strategy to bring about maximum outcomes for both the firm and the society (Basu and Palazzo, 2008). Many studies in consumer markets have also indicated that CSR and corporate reputation induce positive brand perceptions of a corporation's products (Brickley et al, 2002;Jones, 2005;Smith and Higgins, 2000;Varadarajan and Menon, 1988).…”
Section: Introductionmentioning
confidence: 99%